(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines the political and legal issues that have been developed to prevent corruption in public administration. It describes the negative impact of corruption on public administration as a subject of philosophical research. In Uzbekistan, opinions on normative and legal documents developed in this area have been studied scientifically.